A QUESTION OF TRAINING METHODOLOGY: DO WE NEED BACK SQUAT IN THE PREPARATION OF WEIGHTLIFTERS? - Andras S. Szabo (Sport Scientific And Practical Aspects, 2025)
The paper deals with questions of competitive (snatch and clean&jerk) and special assistant exercises (e.g. squats) in weightlifting. Information is given about the difference of the effect of front squat and back squat exercises, concerning the technique and strength development. Attention is paid to the adventages of application of front squat exercises on the trainings of olympic lifters.